The Existence of Islamic Law and Customary Law in the Indonesian National Legal System - Nasution, Suryadi; SA, Saifullah; Asmaret, Desi; Kamal, Tamrin; Julhadi, Julhadi (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2024)
This research examines the existence of Islamic Law and Customary Law in Indonesia's national legal system which reflects legal pluralism in a country with high cultural and religious diversity. The purpose of the research is to explore the role and integration of Islamic Law and Customary Law within the national legal framework, particularly in the context of the application of sharia principles and the recognition of customary law communities. This research utilizes a qualitative descriptive method with analysis of documents, legal literature, and relevant legislation, as well as a historical approach to understand theories of legal acceptance such as Receptie and Receptie in Complexu. The results of the analysis show that Islamic Law has gained significant legitimacy, especially through the Compilation of Islamic Law (KHI) which regulates family law and inheritance. Meanwhile, Customary Law is also recognized in Article 18B of the 1945 Constitution as an important part of the national legal system, although its implementation faces modernization challenges. This research finds that the interaction between these two legal systems produces not only challenges but also opportunities to build a national law that is adaptive and responsive to the needs of society. Thenovelty of this research lies in the comprehensive analysis of the dynamics of harmonization of Islamic Law and Customary Law amidst the social and political complexities in Indonesia. This research emphasizes the importance of an inclusive and contextual approach in building a just and sustainable legal system, which accommodates local religious and cultural values.